Post-Keynesian dynamic stochastic general equilibrium theory - Roger E.A. Farmer (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2017)
This paper explains the connection between ideas developed in my recent books and papers and those of economists who self-identify as post-Keynesians. My own work is both neoclassical and 'old Keynesian.' Much of my published work assumes that people have rational expectations and that 'animal spirits' should be modeled as a new fundamental. I adopt a general equilibrium framework to model the macroeconomy. But although I write from a neoclassical tradition the themes I explore in my published writing have much in common with heterodox economics. This paper explains the common elements between these seemingly disparate traditions. I make the case for unity between post-Keynesian and general equilibrium theory under the banner of post-Keynesian dynamic stochastic general equilibrium theory.
Keywords: B22; B40; E12; E13; E32; 330; post-Keynesian economics; DSGE theory; rational expectations